This commit is contained in:
jverzani 2023-04-26 10:33:54 -04:00
commit e1cfc90e7d

View File

@ -515,7 +515,7 @@ This example shows a useful template:
\begin{align*}
[2x^2 - \frac{x}{3} + 3e^x]' & = 2[\square]' - \frac{[\square]]}{3} + 3[\square]'\\
[2x^2 - \frac{x}{3} + 3e^x]' & = 2[\square]' - \frac{[\square]'}{3} + 3[\square]'\\
&= 2[x^2]' - \frac{[x]'}{3} + 3[e^x]'\\
&= 2(2x) - \frac{1}{3} + 3e^x\\
&= 4x - \frac{1}{3} + 3e^x
@ -552,7 +552,7 @@ This example shows a useful template for the product rule:
### Quotient rule
The derivative of $f(x) = u(x)/v(x)$ - a ratio of functions - can be similarly computed. The result will be $[u/v]' = (u'v - uv')/u^2$:
The derivative of $f(x) = u(x)/v(x)$ - a ratio of functions - can be similarly computed. The result will be $[u/v]' = (u'v - uv')/v^2$:
```{julia}
@ -609,7 +609,7 @@ The same $u$ and $v$ my be identified. The quotient rule readily applies to yiel
$$
f'(x) = u'v - uv' = \frac{\cos(x) \cdot (1 + x^2) - (1 + \sin(x)) \cdot (2x)}{(1+x^2)^2}.
f'(x) = \frac{u'v - uv'}{v^2} = \frac{\cos(x) \cdot (1 + x^2) - (1 + \sin(x)) \cdot (2x)}{(1+x^2)^2}.
$$
---
@ -653,7 +653,7 @@ This pattern generalizes, clearly, to:
$$
[f_1\cdot f_2 \cdots f_n]' = f_1' f_2 \cdots f_n + f_1 \cdot f_2' \cdot (f_3 \cdots f_n) + \dots +
[f_1\cdot f_2 \cdots f_n]' = f_1' f_2 \cdots f_n + f_1 \cdot f_2' \cdot f_3 \cdots f_n + \dots +
f_1 \cdots f_{n-1} \cdot f_n'.
$$
@ -777,14 +777,14 @@ $$
---
Find the derivative of $\log(2 + \sin(x))$. This is a composition $\log(x)$ with derivative $1/x$ and $2 + \sin(x)$ with derivative $\cos(x)$. We get $(1/\sin(x)) \cos(x)$.
Find the derivative of $\log(2 + \sin(x))$. This is a composition $\log(x)$ with derivative $1/x$ and $2 + \sin(x)$ with derivative $\cos(x)$. We get $(1/(2 + \sin(x))) \cos(x)$.
In general,
$$
[\log(f(x))]' \frac{f'(x)}{f(x)}.
[\log(f(x))]' = \frac{f'(x)}{f(x)}.
$$
---
@ -835,8 +835,8 @@ Rearranging:
$$
f(g(a+h)) - f(g(a)) - f'(g(a)) g'(a) h = f'(g(a))\epsilon_g(h))h + \epsilon_f(h')(h') =
(f'(g(a)) \epsilon_g(h) + \epsilon_f(h')( (g'(a) + \epsilon_g(h))))h =
f(g(a+h)) - f(g(a)) - f'(g(a)) g'(a) h = f'(g(a))\epsilon_g(h)h + \epsilon_f(h')(h') =
(f'(g(a)) \epsilon_g(h) + \epsilon_f(h') (g'(a) + \epsilon_g(h)))h =
\epsilon(h)h,
$$
@ -846,7 +846,7 @@ where $\epsilon(h)$ combines the above terms which go to zero as $h\rightarrow 0
##### The "chain" rule
The chain rule name could also be simply the "composition rule," as that is the operation the rule works for. However, in practice, there are usually *multiple* compositions, and the "chain" rule is used to chain together the different pieces. To get a sense, consider a triple composition $u(v(w(x())))$. This will have derivative:
The chain rule name could also be simply the "composition rule," as that is the operation the rule works for. However, in practice, there are usually *multiple* compositions, and the "chain" rule is used to chain together the different pieces. To get a sense, consider a triple composition $u(v(w(x)))$. This will have derivative:
@ -1318,7 +1318,7 @@ Compute the derivative of $x^e$ using `limit`. What do you get?
#| hold: true
#| echo: false
choices = ["``e^x``", "``x^e``", "``(e-1)x^e``", "``e x^{(e-1)}``", "something else"]
answ = 5
answ = 4
radioq(choices, answ, keep_order=true)
```
@ -1418,7 +1418,7 @@ Consider the function $f$ and its transformation $g(x) = f(x - a)$ (shift right
yesnoq("no")
```
Consider the function $f$ and its transformation $g(x) = f(x - a)$ (shift right by $a$). Is $f'$ at $x$ equal to $g'$ at $x-a$?
Consider the function $f$ and its transformation $g(x) = f(x - a)$ (shift right by $a$). Is $g'$ at $x$ equal to $f'$ at $x-a$?
```{julia}
@ -1511,7 +1511,7 @@ answ = 3
radioq(choices, answ)
```
##### Question
###### Question
Their are $6$ trig functions. The derivatives of $\sin(x)$ and $\cos(x)$ should be memorized. The others can be derived if not memorized using the quotient rule or chain rule.
@ -1531,7 +1531,7 @@ trig_choices = [
radioq(trig_choices, 1)
```
What is $[\cot(x)]'$? (Use $\tan(x) = \cos(x)/\sin(x)$.)
What is $[\cot(x)]'$? (Use $\cot(x) = \cos(x)/\sin(x)$.)
```{julia}
@ -1555,7 +1555,7 @@ What is $[\csc(x)]'$? (Use $\csc(x) = 1/\sin(x)$.)
radioq(trig_choices, 4)
```
##### Question
###### Question
Consider this picture of composition:
@ -1598,9 +1598,8 @@ Assuming the approximation gets better for $h$ close to $0$, as it visually does
\begin{align*}
\frac{d(f\circ g)}{dx}\mid_{x=1}
&= \lim_{h\rightarrow 0} \frac{f(g(1) + g'(1)h)-f(g(1))}{h}\\
&= \lim_{h\rightarrow 0} \frac{f(g(1) + g'(1)h)-f(g(1))}{h}\\
&= \lim_{h\rightarrow 0} \frac{f(g(1) + g'(1)h)-f(g(1))}{g'(1)h} \cdot g'(1)\\
&= \lim_{h\rightarrow 0} (f\circ g)'(1) \cdot g'(1).
&= \lim_{h\rightarrow 0} (f\circ g)'(g(1)) \cdot g'(1).
\end{align*}